Extra Academic Activity of Students, Including Employment - Niedzielski, Eugeniusz (Olsztyn Economic Journal, 2016)
With the aim of increasing their opportunities for employment after graduating, during their studies students undertake various activities to expand their competences in the areas of experience, knowledge and skills. Such extra academic activity (EAA) includes voluntary service, activities in student organisations and, increasingly frequently, paid employment. As the survey presented in this paper shows, students undertake employment to generate the means for covering the costs of studies and additional expenses not financed by their parents. This offers students a certain level of financial freedom and simultaneously develops their employee competences. The forms and scope of employment are diversified from permanent employment through different types of fixed term contracts to occasional employment. Availability of full time students defined by the plan of studies is the main limitation to employment. Despite the increasing awareness of the usefulness of professional experience in satisfying the expectations of future employers, some students (25%) do not show any extra academic activity, including in the area of employment.